2014
DOI: 10.1007/s11802-014-2471-2
|View full text |Cite
|
Sign up to set email alerts
|

Macroalgae blooms and their effects on seagrass ecosystems

Abstract: Seagrass decline caused by the macroalgae blooms is becoming a common phenomenon throughout temperate and tropical regions. We summarized the incidence of macroalgae blooms throughout the world and their impact on seagrass beds by direct and indirect ways. The competition for living space and using resources is the most direct effect on seagrass beds when macroalgae are blooming in an aquatic ecosystem. The consequence of macroalgae blooms (e.g., light reduction, hypoxia, and decomposition) can produce signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 99 publications
1
34
0
Order By: Relevance
“…Phase shifts from seagrass-dominated to macroalgae-dominated ecosystems have been well documented in different areas worldwide, such as in Tomales Bay, California, USA (Huntington and Boyer, 2008) and the Mondego estuary, Portugal (Cardoso et al, 2004; for a review see Han and Liu, 2014). The present study showed a rapid (i.e.…”
Section: Discussionsupporting
confidence: 68%
“…Phase shifts from seagrass-dominated to macroalgae-dominated ecosystems have been well documented in different areas worldwide, such as in Tomales Bay, California, USA (Huntington and Boyer, 2008) and the Mondego estuary, Portugal (Cardoso et al, 2004; for a review see Han and Liu, 2014). The present study showed a rapid (i.e.…”
Section: Discussionsupporting
confidence: 68%
“…The algae were not floating on the surface, but they were always found tumbling along the substrate, sometimes attaching to seagrass leaves and shoots; this behavior has already been reported, for the species, in other locations (Flindt et al, 2007). These mats, beside the scouring effect, reduce light availability for seagrass shoots (Krause-Jensen et al, 1996;McGlathery, 2001), increase the sediment organic matter load, inducing the risk of anoxia and sulfide intrusion into meristematic areas of segrasses, therefore restricting seagrass growth (Nelson and Lee, 2001;Thomsen and Wernberg, 2009;Han and Liu, 2014). On the adjacent coral reefs, the presence of the mats was not observed.…”
mentioning
confidence: 68%
“…We suggest that this represents an under-studied topic. While opportunistic macroalgae are known to outcompete seagrass beds in eutrophic systems 4 , 59 , 60 , less attention has been dedicated to the microphytobenthos (MPB) communities which often dominate soft-sediments and could represent a later stage of the succession from vegetated to bare 61 . Even though all the die-off plots showed gradual recovery, our findings nevertheless suggest that biofilm layers can have a significant negative effect on seagrass recovery and may be responsible for an alternative stable state characterised by bare sediment.…”
Section: Discussionmentioning
confidence: 99%